Analysis of Traders’ Knowledge Level on Formalin Detection in Fresh Fish at Tavip Market Binjai City - Adinda Azima Riskiya Sibarani; Yulia Khairina Ashar (Lembaga Penerbitan Fakultas Kesehatan, Universitas Kristen Indonesia Maluku, 2025)
Formalin is a prohibited food additive due to its harmful effects on human health. An inspection conducted by the Indonesian Food and Drug Authority (BPOM) in North Sumatra at Tavip Market, Binjai City, found the presence of formalin in several types of fresh fish being sold. The low level of traders’ knowledge regarding the dangers of formalin is believed to be one of the main factors contributing to its use in fresh fish. This study aimed to analyze the association between traders’ knowledge levels and the presence of formalin in fresh fish at Tavip Market, Binjai City. A quantitative approach with a cross-sectional design was employed. The study population consisted of all 32 fresh fish traders at Tavip Market, selected using a total sampling technique. Data were collected through a validated questionnaire to measure traders’ knowledge levels and laboratory testing using the spot test method to detect formalin in fish. Data analysis was conducted using Fisher’s exact test. The results revealed a significant association between traders’ knowledge levels and the presence of formalin in fresh fish (p-value = 0.021). Low knowledge levels were found to increase the risk of formalin use in fresh fish. Continuous education and intensive supervision by relevant authorities are necessary to reduce the circulation of formalin-contaminated fish in traditional markets.